Effects of Storage Temperature and Spices Incorporation on the Stability and Antibacterial Properties of Fontitrygon margarita (Günther, 1870) Liver Oil - Boris Simo Noutsa; Arlette Danelle Deutchoua Djitieu; Fabrice Fabien Dongho Dongmo; Fabrice Hervé Njike Ngamga; Sammuel Raymond Tchabong; Ousman Tamgue; Rosalie Anne Ngono Ngane; François Tchoumbougnang (Journal of Food Quality)
Fontitrygon margarita liver oil, rich in unsaturated fatty acids, is susceptible to oxidation during storage, which can diminish its antibacterial qualities. This study examines the effects of storage temperature and the addition of spices on the stability and antibacterial properties of F. margarita liver oil. Oils with added spices were stored in opaque bottles at room temperature (28 ± 2°C) and in a refrigerator (4°C) and were periodically analyzed over a six-month period. Standard methods were used to determine oil quality indices; the Fourier transform infrared (FTIR) profile was assessed by spectroscopy; and antibacterial activities were measured using the broth microdilution method. The quality indices, FTIR profile, and antibacterial activities of the oil were evaluated and compared based on the incorporation of spices. The quality indices of oil extracted without a stabilizer and stored at room temperature significantly increased over time. The antibacterial activity of these oils gradually decreased during storage, with the minimal inhibitory concentrations (MICs) on bacterial strains of Escherichia coli (EC 137), Enterobacter cloacae (ENT 119 and ENT 51), and Yersinia enterocolitica (YERB 1) increasing from 16 to 128 mg/ml. Regardless of oil quality indices, oils stored in a refrigerator had lower values and better antibacterial activities than those stored at room temperature ((16 ≤ MIC ≤ 64 mg/ml on the strains of EC 137, YERB 1, ENT 51, and Klebsiella pneumoniae (KL 11)). The inclusion of spices significantly reduced the oxidative reaction in the oils and maintained the antibacterial activities of the tested oils. Given its antibacterial properties, F. margarita liver oil holds significant potential for the nutraceutical industry and could be used as a dietary supplement. This research underscores the importance of proper storage conditions and the use of natural stabilizers in maintaining the quality of such valuable natural resources.